2016
DOI: 10.1016/j.nano.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor microenvironment with PEG-based amphiphilic nanoparticles to overcome chemoresistance

Abstract: Multidrug resistance is one of the biggest obstacles in the treatment of cancer. Several factors involves in drug resistance including enhanced repair mechanisms of drug induced DNA damage, lowered tumor extracellular pH, alteration of cell cycle check points, blockage of apoptosis pathway, poor tumor vasculature and over expression of drug efflux pumps. Recent research studies highlight that tumor microenvironment plays a predominant role in tumor cell proliferation and metastasis. Hence, targeting the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 186 publications
(188 reference statements)
1
80
0
Order By: Relevance
“…Many studies have associated PEG with greater tumor uptake and longer circulation time [62,63]. Besides, PEG contributes to increased par- ticle hydrophilicity, stability, avoidance of plasma protein identification and escape from opsonization and clearance [64]. When comparing tumor exposure to the sum of other organs exposure (Figure 6B), we observed that TE was high, with tumor exposure ranging between 28.3 and 49.0% of the global organ exposure.…”
Section: Evaluation Of the Tumor Targeting Efficiencymentioning
confidence: 79%
“…Many studies have associated PEG with greater tumor uptake and longer circulation time [62,63]. Besides, PEG contributes to increased par- ticle hydrophilicity, stability, avoidance of plasma protein identification and escape from opsonization and clearance [64]. When comparing tumor exposure to the sum of other organs exposure (Figure 6B), we observed that TE was high, with tumor exposure ranging between 28.3 and 49.0% of the global organ exposure.…”
Section: Evaluation Of the Tumor Targeting Efficiencymentioning
confidence: 79%
“…Many studies demonstrated that PEGylated liposomes were able to improve the stability and blood-circulation time, together with low plasma clearance, and low volume of distribution (with minimal interaction with non-tumoural tissues) [64,65,66]. Chen et al [67] showed that plasma protein adsorption onto nanocarrier surfaces on PEG-coated nanocarriers strongly depends on the PEG chain length and density at the nanocarrier surface. …”
Section: Strategies To Prolong the Circulation Timementioning
confidence: 99%
“…6,13 Poly(ethylene glycol) (PEG) is a nonionic and hydrophilic polymer widely used in various therapeutic biological drugs as a drug delivery system. [14][15][16][17] Poly(ethylene glycol)-based copolymers play a potential role as biomedical material for biomedical applications because they are biocompatible, biodegradable, and thermosensitive and have easily controlled properties. 18 In 2008, Mok et al 16 reported the applicability of nanocomplexes of PEG and biomacromolecules (such as proteins, DNA, and carbohydrates) for long-acting and sus-tained-release formulas of therapeutic biologic drugs.…”
mentioning
confidence: 99%
“…18 In 2008, Mok et al 16 reported the applicability of nanocomplexes of PEG and biomacromolecules (such as proteins, DNA, and carbohydrates) for long-acting and sus-tained-release formulas of therapeutic biologic drugs. 16 Chen et al 17 also suggested that PEG-based amphiphilic nanoparticles can be used to overcome multidrug resistance in cancer cells via the development of a new drug delivery system. However, most studies of PEG are limited to the approach of material engineering, and the study of the efficacy of PEG is still inadequate.…”
mentioning
confidence: 99%